Proterozoic structural highs beneath the Mackenzie Mountains, northwest Canada, discovered with filtered potential field and seismic data - Cook, Frederick A. (Geoscience Canada, 2000)
A linear belt of Mesoproterozoic (ca. 1.6 Ga) structural highs, some with more than 6-7 km of subsurface relief, underlies the Mackenzie Mountains in northwestern Canada over a distance of at least 1000 km from southeast to northwest. The trend is visible on isostatic gravity data that were bandpass filtered to wavelengths appropriate for intracrustal features, and on seismic reflection profiles that have images of buried Proterozoic anticlines associated with the gravity highs. The combination of filtered potential field data tied to seismic images of subsurface structure in key areas provides a powerful method to map intracrustal structures at long distances away from cross-sectional profiles. Résumé Une bande linéaire de hauts structuraux du Protérozoïque moyen (ca. 1,6 Ga) est visible sous les monts Mackensie, dans le nord-ouest du Canada, et s’étale sur une distance d’au moins 1 000 km, selon une direction sud-est-nord-ouest; certains de ces hauts dépassant les six à sept km de dénivelé en subsurface. Cette bande linéaire ressort sur le tracé des données gravimétriques isostatique filtrées aux longueurs d’onde correspondant aux éléments intracrustaux, ainsi que sur les profils de réflexion sismique qui donnent des images d’anticlinaux protérozoïques souterrains associés aux hauts gravimé-triques. La combinaison de données filtrées de champs de potentiel, et d’images sismiques des structures de subsurface en des endroits clé constitue une méthode très puissante permettant de dresser la carte de structures intracrustales situées à de grandes distance des profils de coupes.